STRATEGI PENGEMBANGAN PENDIDIKAN KEDISIPLINAN DI MI AL KARIMI TEBUWUNG DUKUN GRESIK - Imroâ€™atus Sholikhah; Atikah Isnaeni; Dita Pratiwi (Almarhalah | Jurnal Pendidikan Islam, 2021)
ABSTRACTThe purpose of this research is to describe the disciplinary education development strategy. This research uses qualitative research, as well as a descriptive approach to research. The results of this study indicate that the disciplinary conditions of students at MI Al Karimi Tebuwung Dukun Gresik have been running well. It can be seen that all program activities have been carried out properly and all residents of MI Al Karimi Tebuwung Dukun Gresik are actively involved in implementing them. Many students have implemented discipline without having to be instructed and teacher guidance also has a very big influence on the student discipline process, and this is the key to success in implementing discipline at MI Al Karimi. The supporting and inhibiting factors for the implementation of disciplinary education at MI Al Karimi Tebuwung Dukun Gresik: a) There is direct control from the head of the madrasah and the teacher council b) There is an active role from the parents of students c) the influence of the bad environment d) the presence of some teachers who are static . As explained by the Deputy Head of Madrasah for Curriculum Sector, the strategy for developing disciplinary education at MI Al Karimi Tebuwung Dukun Gresik is: a) Preparation of vision, mission, motto, and objectives b) Preparation of special activity programs c) Rules d) Socialization e) Approach f) Facilities and Infrastructure g) Evaluation.Â Keywords: Strategy, Discipline, Education